Multiple organ dysfunction after trauma. Issue 4 (6th November 2019) - Cole, E; Gillespie, S; Vulliamy, P; Brohi, K; Akkad, H; Apostolidou, K; Ardley, R; Aylwin, C; Bassford, C; Bonner, S; Brooks, A; Cairns, T; et al.
Abstract: Background: The nature of multiple organ dysfunction syndrome (MODS) after traumatic injury is evolving as resuscitation practices advance and more patients survive their injuries to reach critical care. The aim of this study was to characterize contemporary MODS subtypes in trauma critical care at a population level. Methods: Adult patients admitted to major trauma centre critical care units were enrolled in this 4-week point-prevalence study. MODS was defined by a daily total Sequential Organ Failure Assessment (SOFA) score of more than 5. Hierarchical clustering of SOFA scores over time was used to identify MODS subtypes. Results: Some 440 patients were enrolled, of whom 245 (55·7 per cent) developed MODS. MODS carried a high mortality rate (22·0 per cent versus 0·5 per cent in those without MODS; P < 0·001) and 24·0 per cent of deaths occurred within the first 48 h after injury. Three patterns of MODS were identified, all present on admission. Cluster 1 MODS resolved early with a median time to recovery of 4 days and a mortality rate of 14·4 per cent. Cluster 2 had a delayed recovery (median 13 days) and a mortality rate of 35 per cent. Cluster 3 had a prolonged recovery (median 25 days) and high associated mortality rate of 46 per cent. Multivariable analysis revealed distinct clinical associations for each form of MODS; 24-hour crystalloid administration was associated strongly with cluster 1 ( P = 0·009), traumatic brain injury with cluster 2 ( P = 0·002) and admission shock severity with cluster 3 ( P = 0·003). Conclusion: Contemporary MODS has at least three distinct types based on patterns of severity and recovery. Further characterization of MODS subtypes and their underlying pathophysiology may lead to future opportunities for early stratification and targeted interventions. Graphical Abstract: As trauma practice advances, postinjury multiple organ dysfunction syndrome (MODS) is changing. The aim of this study was to characterize contemporary MODS in trauma critical care. Three patterns of MODS were identified, all present on admission, with distinct clinical associations. SOFA, Sequential Organ Failure Assessment. Present from admission with subtypes having different patterns of recovery